Respirometric assessment of biodegradation characteristics of the scientific pitfalls of wastewaters - Orhon, D.; Insel, G.; Karahan, O. (IWA Publishing, 2007)
This paper provides an overview of common problems encountered when using oxygen uptake rate (OUR) measurements for the assessment of wastewater characteristics and process kinetics. Emphasis is placed upon pitfalls that would lead to significant errors. It covers model dependency of the OUR measurements and the need to select appropriate models; interpretation of OUR perturbations as a way to identify new model components and processes; the need for simultaneous observation of relevant model components and multicomponent modelling for appropriate evaluation of OUR measurements; parameter identifiability problems and the effect of active biomass concentration and the endogenous decay rate on model simulation and calibration. Relevant experimental OUR data from previous studies are presented to illustrate and underline common scientific pitfalls.
Keywords: Kinetics; Biodegradation, Environmental; Oxygen Consumption; Bacteria; Sewage; Models, Biological; Chemistry Techniques, Analytical